Plant Tissues as 3D Natural Scaffolds for Adipose, Bone and Tendon Tissue Regeneration - Contessi Negrini, Nicola; Toffoletto, Nadia; Farè, Silvia; Altomare, Lina (Frontiers in Bioengineering and Biotechnology, 2020)
Decellularized tissues are a valid alternative as tissue engineering scaffolds, thanks to the three-dimensional structure that mimics native tissues to be regenerated and the biomimetic microenvironment for cells and tissues growth. Despite decellularized animal tissues have long been used, plant tissue decellularized scaffolds might overcome availability issues, high costs and ethical concerns related to the use of animal sources. The wide range of features covered by different plants offers a unique opportunity for the development of tissue-specific scaffolds, depending on the morphological, physical and mechanical peculiarities of each plant. Herein, three different plant tissues (i.e., apple, carrot, and celery) were decellularized and, according to their peculiar properties (i.e., porosity, mechanical properties), addressed to regeneration of adipose tissue, bone tissue and tendons, respectively. Decellularized apple, carrot and celery maintained their porous structure, with pores ranging from 70 to 420 μm, depending on the plant source, and were stable in PBS at 37°C up to 7 weeks. Different mechanical properties (i.e., Eapple = 4 kPa, Ecarrot = 43 kPa, Ecelery = 590 kPa) were measured and no indirect cytotoxic effects were demonstrated in vitro after plants decellularization. After coating with poly-L-lysine, apples supported 3T3-L1 preadipocytes adhesion, proliferation and adipogenic differentiation; carrots supported MC3T3-E1 pre-osteoblasts adhesion, proliferation and osteogenic differentiation; celery supported L929 cells adhesion, proliferation and guided anisotropic cells orientation. The versatile features of decellularized plant tissues and their potential for the regeneration of different tissues are proved in this work.